Moran Brothers Co. shipyards building steamboats for service in the Klondike gold rush, 1898 - University of Washington Libraries. Special Collections Division. (1898)
Completed May 25, 1898. Caption on image: Twelve Yukon River steamers built by Moran Bros. Company, Seattle, Wash. 1898. Length 175', beam 35', depth 61/2' To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number